2006
DOI: 10.1063/1.2336594
|View full text |Cite
|
Sign up to set email alerts
|

Sterilization mechanism for Escherichia coli by plasma flow at atmospheric pressure

Abstract: A mechanism for sterilizing Escherichia coli by a flowing postdischarge and UV radiation of argon plasma at atmospheric pressure was investigated by analyzing the surviving cells and the potassium leakage of cytoplasmic material and by morphological observation. Inactivation of E. coli results from the destruction of the cytoplasmic membrane and the outer membrane under plasma exposure and the destruction of nucleic acids by exposure to ultraviolet radiation from the plasma source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
58
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 6 publications
1
58
0
Order By: Relevance
“…Indeed encouraged by their potential as a bactericidal technique, 2 low-temperature gas discharges have been studied extensively for bacterial inactivation both in a vacuum chamber at low pressures [3][4][5][6] and in open air at atmospheric pressure. [7][8][9][10][11][12] Much has been learnt of the bactericidal capability and related physical mechanisms of low-temperature plasmas. 13 By contrast, there are very few reports on their ability to destruct proteinaceous matters [14][15][16] and all reported are limited to the use of vacuum plasmas.…”
mentioning
confidence: 99%
“…Indeed encouraged by their potential as a bactericidal technique, 2 low-temperature gas discharges have been studied extensively for bacterial inactivation both in a vacuum chamber at low pressures [3][4][5][6] and in open air at atmospheric pressure. [7][8][9][10][11][12] Much has been learnt of the bactericidal capability and related physical mechanisms of low-temperature plasmas. 13 By contrast, there are very few reports on their ability to destruct proteinaceous matters [14][15][16] and all reported are limited to the use of vacuum plasmas.…”
mentioning
confidence: 99%
“…E. coli seeded on an agar was disinfected within 20 seconds. Sato et al reported the disinfection efficacy of a coaxial microwave (2.45 GHz) Ar plasma flow at atmospheric pressure against E. coli filtered onto membrane filters [6]. They found that E. coli was disinfected by exposure to the plasma flow for 2 min.…”
Section: Resultsmentioning
confidence: 99%
“…It is considered that the short exposure distance is the reason for realizing a short exposure time in our method com- pared with conventional methods. For microwave-induced plasma, the exposure distance was as long as 124 mm [6]. It is considered that the distance is set long to suppress the disinfection by heat due to the high temperature of microwave-induced plasma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For sterilization, there are reports on the inactivation of bacteria, such as Escherichia coli [5,6], Micrococcus luteus [7], and Staphylococcus aureus [8], using atmospheric-pressure plasma and on the disruption of Bacillus subtilus spores [9,10] and Bacillus atrophaeus spores [11,12]. For medical applications, it was reported that the irradiation of mammalian cells with atmospheric-pressure plasma caused their necrosis [13] or apoptosis [14] depending on the irradiation conditions.…”
Section: Introductionmentioning
confidence: 99%